Enhanced removal of Cr(VI) using a modified environment-friendly adsorbent - Shan Liu (IWA Publishing, 2021)
Chitosan (CS) was modified with ferric chloride hexahydrate (FeCl3·6H2O) and sodium laurylsulfonate (SLS) to prepare the compound adsorbent CS-Fe-SLS. Taking Cr(VI) as the target pollutant, the influence of different factors (solution pH, adsorption time, initial adsorption concentration and coexisting ions) were investigated. The results showed that the optimal pH value was 3.0; the adsorption equilibrium was reached at 120 min, with both physical and chemical process being involved in the adsorption process; the maximum adsorption value was 131.91 mg/g, with the adsorption being both single-layer and multi-layer adsorption; Cl−, NO3- and SO42- had little effect on adsorption, CO32- reduced it and Cu(II) increased it. The characterization results of scanning electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction showed that CS-Fe-SLS and chitosan had different morphological characteristics: in contrast with chitosan, CS-Fe-SLS had a larger volume and more flakes on the surface. CS-Fe-SLS was significantly lower in crystallinity than chitosan, and was more irregular and amorphous in shape, and the experimental results showed that CS-Fe-SLS had better adsorption capacity for Cr(VI). The adsorption Cr(VI) was related to -NH and -OH on the material. Some Cr(VI) was reduced to Cr(III) during the adsorption process.